(untitled) (CIPEEX, 2025)
Meningitis is an inflammatory process of the meninges, the three layers that surround the brain and protect the encephalon, spinal cord and other areas of the nervous system. It is usually caused by bacteria or viruses, but can also be caused by parasites, fungi or Koch’s bacteria, which is responsible for tuberculosis. The concentration of people is the main factor in transmission because it is transmitted directly from person to person. When talking, sneezing or coughing, the sick person expels drops of saliva containing the infectious agent, called Mycobacterium tuberculosis or Koch’s bacillus, which can be aspirated by another person and contaminate them. The objective of this study was to analyze children under the age of one year to nine years who were infected with meningitis between 2010 and 2020, highlighting the significant number of cases, which is considered a public health problem in Brazil. The approach used in this study was an integrative literature review, which allowed a complete analysis of the signs, symptoms and methods of spreading meningitis. The PICO method was used to formulate the main question, guiding the search in specific databases and resulting in the careful selection of relevant articles. The detailed analysis of the chosen studies highlights the importance of awareness and prevention, especially through vaccination, to reduce the impacts of the disease. The data analyzed highlights that in 2020 there was a large increase in cases of meningitis, whose main risk factors for poor results include an increase in cases due to the large number of infected people in a given location, the diagnosis is carried out by clinical and also laboratory means, for treatment and to avoid death.Keywords: Meningitis; Bacteria; Infectious; Health.BibliographyGUIMARÃES, Nara Moraes et al. Análise epidemiológica dos casos de meningite em crianças no Brasil dos anos 2010 a 2020. Research, Society and Development, v. 11, n. 15, p. e187111537032-e187111537032, 2022. link: https://rsdjournal.org/index.php/rsd/article/view/37032/30903ANELI, M. B.; TAVARES AMADEU, L. .; VENDRAMINI GOYOGI DE PAULA, J. V.; PEREIRA SOUTO NETO, L. .; SANTOS DE CARVALHO, L. .; ZUMBA FLORES, S.; CRISTINA COLA, P. The main morbidities and mortality rates in bacterial meningitis: As principais morbidades e o índice de mortalidade na meningite bacteriana. Concilium, [S. l.], v. 24, n. 9, p. 327–339, 2024. DOI: 10.53660/CLM-3386-24I12. Disponível em: https://www.clium.org/index.php/edicoes/article/view/3386.